AMIGO—A Socially Assistive Robot for Coaching Multimodal Training of Persons with Dementia - Paletta, Lucas; Schüssler, Sandra; Zuschnegg, Julia; Steiner, Josef; Pansy-Resch, Sandra; Lammer, Lara; Prodromou, Dimitrios; Brunsch, Sebastian; Lodron, Gerald; Fellner, Maria (Social Robots: Technological, Societal and Ethical Aspects of Human-Robot Interaction, 2019)
In the context of assistive robotics in health care, we introduce the AMIGO system with its innovative “Coach” framework that uses social robots for the entertaining motivation of persons with Dementia. The overarching objective is to empower persons with Dementia to perform daily stimulating training activities within the concept of an integrated multimodal intervention. The “Coach” frame is complemented by a “Companion” frame that involves the client in a long-term relationship with the robot which will care by asking about the client’s health status, remind about important events or tasks, involve the client in dialog, invite the client to engage in multimodal training, and provide entertainment such as reading the news from all over the world. A research objective is to adjust Pepper’s dialog and motivation style based on emotional feedback sensed in interaction. The system will motivate the client to perform personalized exercises and to maintain and extend social bonds and will stimulate cognitive processes and physical activities. Sensors for eye tracking and motion analysis technologies will offer affordances for entertaining, sensorimotor sequences and for data capture and analysis of cognition and locomotion-specific behavioral parameters. Easily usable interfaces enable planning and autonomous daily practice to formal as well as to the informal caregiver in a weekly rhythm so that people with Dementia can stay at home longer and the progress of Dementia is slowed down. The AMIGO system is motivated from the viewpoint of health care, neuropsychology, and ICT systems. The first implementation of the prototype system and first results of a mixed-method study are presented in detail.